Labor supply as a discrete choice among latent jobs: Unobserved heterogeneity and identification - John K. Dagsvik; Zhiyang Jia (Statistics Norway, Research Department, 2014)
This paper discusses aspects of a framework for modeling labor supply where the notion of job choice is fundamental. In this framework, workers are assumed to have preferences over latent job opportunities belonging to worker-specific choice sets from which they choose their preferred job. The observed hours of work and wage is interpreted as the job-specific hours and wage of the chosen job. The main contribution of this paper is an analysis of the identification problem of this framework under various conditions, when conventional cross-section micro-data are applied. The modeling framework is applied to analyze labor supply behavior for married/cohabiting couples using Norwegian micro data. Specifically, we estimate two model versions with in the general framework. Based on the empirical results, we discuss further qualitative properties of the model versions. Finally, we apply the preferred model version to conduct a simulation experiment of a counterfactual policy reforms.
Keywords: J22; C51; 330; labor supply; non-pecuniary job attributes; latent choice sets; random utility models; identification